Respuesta :

Answer:

u=9

Step-by-step explanation:

I combined like terms and used pemdas

Ver imagen kearra31

Answer:

[tex]u=-9/7[/tex]

Step-by-step explanation:

Given equation:

[tex]5u+3-2(-6u-6)=3(u-1)[/tex]

Solving the brackets

           [tex]5u+3-2(-6u)-2(-6)=3(u)-3(1)[/tex]

                [tex]5u+3+12u+12=3u-3[/tex]

Taking the terms of u to one side and to find the value of u

               [tex]5u+12u-3u=-3-3-12[/tex]

                              [tex]14u=-6-12\\14u=-18\\u=-18/14\\[/tex]

On simplifying by dividing numerator and denominator by 2

                              [tex]u=-9/7[/tex]